2011
DOI: 10.1177/1359105311417194
|View full text |Cite
|
Sign up to set email alerts
|

Communication and culture: Predictors of treatment adherence among Mexican immigrant patients

Abstract: This study examined communication and culture in clinicians' interactions with Mexican immigrants in Texas. Specifically, we explore the unique interplay among levels of acculturation, beliefs about culturally-based medical practices, perceptions of medical encounters, and the likelihood of adherence to medical therapy recommendations from US providers. Results suggest that: (a) acculturation predicts perceptions of out-group membership in the patient-provider interaction; (b) beliefs about complementary and a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
18
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(20 citation statements)
references
References 27 publications
2
18
0
Order By: Relevance
“…opportunities for health screening and education; locations for accessing healthy foods). Recent research suggests that communication between patients and medical providers may be especially important in promoting engagement and treatment adherence among Latinos (Villagran et al, 2012), so it is essential that providers present health recommendations in a clear and culturally appropriate manner. Along these lines, Mohan et al (2013) suggested that illustrated diabetes management instructions may be useful with Latino patients as a supplement to traditional verbal or written directions, particularly for patients who speak limited English.…”
Section: Discussionmentioning
confidence: 99%
“…opportunities for health screening and education; locations for accessing healthy foods). Recent research suggests that communication between patients and medical providers may be especially important in promoting engagement and treatment adherence among Latinos (Villagran et al, 2012), so it is essential that providers present health recommendations in a clear and culturally appropriate manner. Along these lines, Mohan et al (2013) suggested that illustrated diabetes management instructions may be useful with Latino patients as a supplement to traditional verbal or written directions, particularly for patients who speak limited English.…”
Section: Discussionmentioning
confidence: 99%
“…105,120,124–127 Cultural competence and literacy among providers, a significant factor for effective patient-provider communication, has been linked with improved patient decision making, patient communication, and adherence to treatment. 128 Training for providers in cultural competence and cultural literacy includes knowledge and skill development in the use of patient beliefs, customs, and world views to frame health information. 129 Provider cultural competence is perceived to be high when the practitioner is able to speak even some Spanish and can affect the content of the interaction.…”
Section: Commonalities In Language and Cultural Beliefs Among Us Hispmentioning
confidence: 99%
“…130,131 One recent study examined the role of culture and healthcare interaction among Mexican immigrants and found that adherence decisions were associated with patients’ beliefs about the physician’s cultural literacy and identity. 128 …”
Section: Commonalities In Language and Cultural Beliefs Among Us Hispmentioning
confidence: 99%
“…Nevertheless, to analyze the phenomenon of adherence, especially to drugs, is also complex. This measure of clinical outcome is conditioned by multiple factors that transcend doctors and the patients, and that is why clinicians would reach better levels of adherence by using their communicative behaviors and empathic sensibility in a conscious and articulated way [14][15][16][17][18].…”
Section: Verbal Communicationmentioning
confidence: 99%